Kepemimpinan, Budaya Organisasi Sekolah, Kompetensi dan Komitmen Guru Serta Implikasinya Terhadap Kinerja Guru - Darwin Lie (Kontigensi : Jurnal Ilmiah Manajemen, 2016)
The purpose of this study was to analyze the influence of the principal leadership, the school organizational culture, the competence of teachers on the motivation and the commitment of teachers and its implication to the performance of teachers ( study on SMA teachers in five regency – city in the Province Of North Sumatra). This Research is done by using descriptive and verificative method. As for sampling technique used Cluster random Sampling, and by using the formula of determination sample developing by Isaac and Michael, with the population as much 4.486 people and obtained sample as much 255 responden. As for Analyzer used Path Analysis. Result of inferential research as follows :There are significant influence from all Independent variable to The Motivation of Teachers. There are significant influence from all independent variable to The Commitment of Teachers.There are significant influence from variable of the Motivation of Teacher and the Commitment of Teacher to The Performance of Teachers.Result of research conclude that to increase the Performance of teachers, need to increase the Principal’s Supervision on Academic to teacher, need to apply The Regulation of discipline consistently, need to increase the motivation of teachers as a group, need to increase the commitment of teachers to improve the quality of students, and also need to increase the exploitation of learning strategy of teachers.